Antibacterial performance of glucose-fructose added MW based zirconia coatings – Possible treatment for bone infection. (April 2020) - Sanaullah, Ifra; Bukhari, Bushra S.; Batool, Tanzeela; Riaz, Saira; Khan, Hira N.; Sabri, Anjum N.; Naseem, Shahzad
Abstract: Use of ceramic coatings has increased dramatically in orthopedics by improving their wear resistance and consequent long-term stability. Such stability involves not only the strength of material but also its resistance toward bacterial attacks. Amongst all ceramics, zirconia is selected in the present study due to its white color and high value of hardness making it a potential candidate to be used as implants and their coatings. In the present study effect of varying microwave powers (i.e. 100W, 200W, 300W, 400W, 500W, 600W, 700W, 800W, 900W and 1000W) on sol–gel synthesized glucose and fructose added zirconia coatings has been investigated. Formation of mixed tetragonal – monoclinic phases has been observed at relatively low microwave powers, i.e. 100–500W. However, at 600–1000W phase pure tetragonal zirconia is observed without any post heat treatment. FTIR analysis confirms formation of tetragonal phase of zirconia at 600–1000W microwave power. XPS results confirm the binding energies of Zr 3d and O 1s of microwave assisted zirconia coatings. High value of transmittance, i.e. ~90%, is observed at higher microwave powers. Variation in microwave powers is observed to tune the energy band gap of zirconia coatings in the range of 4.2–5.1 eV. Dielectric constant of 8–10 at log f  = 4 is observed. High value of hardness and fracture toughness i.e. 1231 HV and 24.85 MPam −1/2, respectively, is observed for stabilized tetragonal zirconia coatings. Stabilized glucose fructose added zirconia shows strong antioxidant activity. Zirconia coatings are tested against Staphylococcus aureus bacteria for their potential application to treat bone infection. Results suggest that stabilized tetragonal zirconia can be successfully employed for orthopedic coatings. Graphical abstract: Image 1 Highlights: Glucose–fructose added zirconia (ZrO2 ) coatings were prepared via microwave (MW)-assisted sol-gel method. Mixed phases were observed at MW powers of 100-500W, whereas pure tetragonal phase was observed at 600-1000W. High transmission along with direct tuning of band gap (4.2 - 5.1 eV) was observed with variation in microwave power. Dielectric constant (8-10) at log f = 4 along with high hardness & fracture toughness was observed. Strong antioxidant & antibacterial response was observed suggesting potential application of ZrO2 to treat bone infection.